Kepuasan Kerja dalam Perspektif Pendidikan Islam - Ana Mega Selviani; Annisa Zauhar Nafisah; Salsabila Shafha Firabiawwalia; Nirva Diana (CV. Creative Tugu Pena, 2024)
This article discusses job satisfaction from an Islamic education perspective. Job satisfaction is an important aspect in the world of work. The level of employee satisfaction can affect productivity, motivation and employee turnover rates. Job satisfaction is an important factor in every job which is an affective or emotional side. Job satisfaction is basically a psychological aspect that reflects a person's feelings towards his job, he will feel satisfied with the suitability of his abilities, skills and expectations with the job he is facing. This article uses a library research analysis method which relies on data sources in the form of books/books, scientific articles in journals, research results, and print media opinions related to the discussion theme, namely Job Satisfaction in an Islamic Education Perspective. The results of this research show that in carrying out our daily work in order to achieve job satisfaction, we should always synergize feelings of sincerity, patience and gratitude so that in our work we can maximize the potential that exists within us without always looking at the material, self-evaluation and conduciveness of superiors. for those who are incompetent, and others, for them it is not a disaster, but rather a test promised by Allah SWT which will result in increasing the quality (awareness) of faith in work, so that life remains optimistic about moving forward, instead of giving up on circumstances